2021
DOI: 10.2478/cee-2021-0034
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ventilation and Shading Control on the Result of Summer Overheating Simulation

Abstract: The most suitable methods for increasing the climate resistance of buildings on hot summer days are intensive ventilation and effective external shading. However, it is possible to discuss what kind of approach used, while simulating the control of these two elements in energy simulation programs, to make the result as much representative as possible. We created and compared three different control modes for this purpose. The basic mode represented models created from monitoring of habits of building users, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The linear fitting (red line) is quite straightforward, as can be anticipated -humans work and learn better when they are satisfied with their indoor environment. Despite a large number of factors influencing human sensations and perceptions, thermal environment and heat transfer issues might be considered as a dominant force [15][16][17][18][19][20][21]. However, an important element is also noise [22] and future studies might be focused on this aspect due to its possible impact on the general sensations and productivity.…”
Section: Resultsmentioning
confidence: 99%
“…The linear fitting (red line) is quite straightforward, as can be anticipated -humans work and learn better when they are satisfied with their indoor environment. Despite a large number of factors influencing human sensations and perceptions, thermal environment and heat transfer issues might be considered as a dominant force [15][16][17][18][19][20][21]. However, an important element is also noise [22] and future studies might be focused on this aspect due to its possible impact on the general sensations and productivity.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the influence of external climatic conditions [14] significantly affects the state of the indoor environment of the room under study. For buildings built in passive standard, the dominant season is not the heating season, but the cooling season with higher financial requirements for the operation of the building [15].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results, it is a common partial conclusion that the tested concept of the retrofitting of the transparent system has shown a high potential in connection with the elimination of heat gain from solar radiation. However, the shading element of the window should be movable, as being fixed it would cause excessive space cooling in summer [24].…”
Section: Civil and Environmental Engineeringmentioning
confidence: 99%